THE EFFECT OF THE SIZE AND SHAPE OF WOOD PARTICLES ON THE TENSILE STRENGTH PERPENDICULAR TO THE PLANE OF THE PARTICLEBOARD: EXPERIMENTS AND MODELING - Vasiliev, Sergey; Panov, Nikolai; Dospekhova , Natalia; Rakovskaya, Marina; Pronin, Ilya; Kolesnikov, Gennady (Journal of Applied Engineering Science, 2021)
One of the problems of sustainable development is the technologies improvement for the rational use of wood and other raw materials of plant origin. The literature reflects a large amount of applied research that was conducted to justify new technologies for the production of particle boards (PB). The main attention in the known works is paid to the influence of the particle size distribution on the strength of PB. The influence of particle shape on the PB strength has been studied to a lesser extent. In this regard, this article considers the influence of the shape and size of particles on the tensile strength perpendicular to the plane of the PB. A geometric analysis of the particle shape is performed. It was taken into account that the PB strength depends on the shape and size of the particles, as well as on the number of adhesive contacts between particles. To obtain quantitative estimates, formulas were substantiated confirming that an increase in the length of the particles and a decrease in their transverse dimensions lead to an increase in the PB strength. Experimental research methods were used, and mathematical modeling of the sample failure area was performed.
Keywords: engineering; modeling; composite material; particle board; tensile strength